2017
DOI: 10.1093/annonc/mdw560
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality treatment for esophageal adenocarcinoma: multi-center propensity-score matched study

Abstract: BackgroundThe primary aim of this study was to compare survival from neoadjuvant chemoradiotherapy plus surgery (NCRS) versus neoadjuvant chemotherapy plus surgery (NCS) for the treatment of esophageal or junctional adenocarcinoma. The secondary aims were to compare pathological effects, short-term mortality and morbidity, and to evaluate the effect of lymph node harvest upon survival in both treatment groups.MethodsData were collected from 10 European centers from 2001 to 2012. Six hundred and eight patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 28 publications
8
59
2
1
Order By: Relevance
“…RM approach was a safe option for locally advanced ESCC, which was consistent with the conclusion from previous studies mainly focusing on esophageal adenocarcinoma. Previous studies have found that nCRT improved pathological complete response (pCR) rate and reduced lymph node metastases rate when compared to nCT (21,(23)(24)(25). The latest NeoRes trial (26) also confirmed the outcomes in ESCC subgroups.…”
Section: Discussionmentioning
confidence: 84%
“…RM approach was a safe option for locally advanced ESCC, which was consistent with the conclusion from previous studies mainly focusing on esophageal adenocarcinoma. Previous studies have found that nCRT improved pathological complete response (pCR) rate and reduced lymph node metastases rate when compared to nCT (21,(23)(24)(25). The latest NeoRes trial (26) also confirmed the outcomes in ESCC subgroups.…”
Section: Discussionmentioning
confidence: 84%
“…Multimodality treatment has become increasingly used for EC, which proved to have good outcomes (5). Neoadjuvant chemoradiotherapy was proved to be a better strategy for local advanced patients (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…1 In a recent, large European cohort of stage II and III esophago-gastric junction and esophageal adenocarcinoma, the 3-year overall survival rate was 55% and a 3-year disease-free survival was 50% after multimodal therapy. 27 Thus, after definitive treatment of esophageal cancer, patients are still at high risk for recurrence. A recent, large American study reported that recurrence occurred more frequently in the first year after surgery and they were distant in 55% of cases, locoregional in 28%, or both in 17%.…”
Section: Resultsmentioning
confidence: 99%